Bat diversity of the Serranía de San Lucas (Bolívar and Antioquia), northern Colombia - Solari, Sergio; Gómez-Ruiz, Daisy; Patiño-Castillo, Edilson; Villada-Cadavid, Tomás; López M, Carolina (THERYA, 2019)
Serranía de San Lucas is an isolated mountain ridge in the Northern Andes, reaching above 2,500 masl, located between the Central and the Eastern Cordilleras in northeast Colombia, including parts of Bolívar and Antioquia departments. Due to its particular location and difficult access, there are few studies on its biological diversity. In order to clarify the geographical affinities of its bat fauna, we conducted a survey at four representative localities of this mountain range. Between 2015 and 2017, we conducted four assessments to characterize the bat species richness in San Lucas; these localities represent the dominant habitats in the area, including lowland and premontane forests, and swamps. We used three to six mist nets per night, between 17:30 and 23:00 h and identified species in the field, collecting specimens to corroborate and document the diversity in each location. Species accumulation curves and non-parametric estimators assessed efficiency of sampling; in addition, Jaccardâ€™s similarity index was used to assess beta diversity. Each species was assigned to a trophic guild for ecological analyses and comparisons of the assemblages. We recorded 47 species from six families (Table 2), with Phyllostomidae being the most diverse (35 species). Although species richness at a local scale varied between 14 and 23 species, the heterogeneity among them shows a particular richness for San Lucas as a whole. A notable geographic record was Mimon cozumelae, which extends its known distribution in northern South America, while other four species are confirmed for the Magdalena Valley, reinforcing a trans-Andean influence. Our records reinforce a biogeographical connection with the region of Chocó-Nechí-Magdalena (sensu Hernández-Camacho et al. 1992), thus contributing to validation of the perception that San Lucas shows greater affinity to the Central Cordillera than to the Eastern one. It is evident that several groups (i. e., insectivorous) have not been fully sampled, and that new methods (diurnal roost searches and acoustical sampling) and longer survey efforts might reveal more additions to this list. Our study reveals some peculiarities in the diversity of bats of Serranía de San Lucas, including species typical of inter-Andean valleys and suggesting an influence of the trans-Andean zone, resulting in major similarities to assemblages from northwestern Colombia and South America, but with a specific composition that is indicative of the good state of conservation of the habitats in the study area and its relevance as a future, and necessary, protected area for the country.